Photo-fermentative hydrogen production from crop residue: A mini review. (April 2017) - Zhang, Quanguo; Wang, Yi; Zhang, Zhiping; Lee, Duu-Jong; Zhou, Xuehua; Jing, Yanyan; Ge, Xumeng; Jiang, Danping; Hu, Jianjun; He, Chao
Highlights: Technology of bio-hydrogen production from crop residues were reviewed. Pretreatment methods and substrate structure were discussed. Hydrogen from pure bacteria, consortia and mutants were discussed. Geometry, light source and mass transfer properties of bioreactor were reviewed. Abstract: Photofermentative hydrogen production from crop residues, if feasible, can lead to complete conversion of organic substances to hydrogen (and carbon dioxide). This mini review lists the studies on photofermentative hydrogen production using crop residues as feedstock. Pretreatment methods, substrate structure, mechanism of photosynthetic bacteria growth and metabolism were discussed. Photofermentative hydrogen production from pure culture, consortia and mutants, and the geometry, light sources, mass transfer resistances and the operational strategies of the photo-bioreactor were herein reviewed. Future studies of regulation mechanism of photosynthetic bacteria, such as highly-efficient strain breeding and gene reconstruction, and development of new-generation photo-bioreactor were suggested.